2022
DOI: 10.1007/s12283-022-00378-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of response behavior in karate kumite between real world and virtual reality

Abstract: Virtual reality is increasingly applied to support physical training and improve athletes’ performance in sports. Nevertheless, there is a research deficit in that, especially in martial arts, it has not yet been shown to what extent the response behavior of athletes in virtual reality is the same as in the real world. If this can be confirmed, a transfer of VR-adapted skills to RW can be expected and sports training in a virtual environment can be applied to improve sports performance. Since the response beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Τhe studies were conducted from 2018 to 2022, a finding which is in full agreement with the results of a recent bibliometric analysis [25]. Most of the studies, with regards to the main variables included, followed a quantitative methodology [20,21], [23,26,27], one followed a qualitative methodology [22], and one was a mixed-method study [24]. Most of the studies demonstrated good methodological quality in terms of design, data collection, and reporting (for more details, see Appendix A).…”
Section: Study Quality and Characteristicssupporting
confidence: 80%
See 4 more Smart Citations
“…Τhe studies were conducted from 2018 to 2022, a finding which is in full agreement with the results of a recent bibliometric analysis [25]. Most of the studies, with regards to the main variables included, followed a quantitative methodology [20,21], [23,26,27], one followed a qualitative methodology [22], and one was a mixed-method study [24]. Most of the studies demonstrated good methodological quality in terms of design, data collection, and reporting (for more details, see Appendix A).…”
Section: Study Quality and Characteristicssupporting
confidence: 80%
“…A summary of the key characteristics and relevant findings of each of the included articles is included in Table 4. The assessment instruments and methodologies utilized in these studies exhibited a diverse spectrum, featuring techniques such as reaction time assessments [20,21,26], motion capture technology [20,23,27], performance analysis [21,26], scoring systems [23], and qualitative evaluations [22,24]. A summary of the key characteristics and relevant findings of each of the included articles is included in Table 4.…”
Section: Study Quality and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations